Plans, Awareness, Reasons, and Experiences (PARE) on Volunteerism of Undergraduates During the COVID-19 Pandemic - Ballesteros, Joebert D; Gismundo, Great I Am W C; Camara, Jun S (ASEAN Multidisciplinary Research Journal, 2023)
Why undergraduates volunteer and how we could harness this to identify policies for curricular integration and volunteer programs is a key factor in community empowerment. This study identified key areas on volunteerism among undergraduates (n=753) in a state university in Pangasinan, Philippines using a survey based on the Voluntary Functional Inventory (VFI) from May to July 2022. Salient findings include the relationship observed between campus student leadership and their awareness, experience, and plans to initiate or participate in voluntary works making this variable a key element in the success of a volunteer program. Further, the male and female did not differ in their perception on awareness and future plans to either initiate or participate in a volunteer program, except that they differed in their actual experience on volunteering during the pandemic. Furthermore, the ‘feeling that it is important to help others’ topped the reasons on why they volunteer. As to correlates, the Social aspect of the VFI registered a significant relationship with degree, year level and field major except for gender and leadership. All the other areas (i.e. protective, values, career, understanding, and enhancement) registered no significant relationship which, when taken together, could serve as significant inputs to a volunteer program and in the lens of curriculum integration.